2011
DOI: 10.1111/j.1365-2052.2011.02293.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in PLAG1 associates with early life body weight and peripubertal weight and growth in Bos taurus

Abstract: Variation at the pleiomorphic adenoma gene 1 (PLAG1) locus has recently been implicated in the regulation of stature and weight in Bos taurus. Using a population of 942 outbred Holstein-Friesian dairy calves, we report confirmation of this effect, demonstrating strong association of early life body weight with PLAG1 genotype. Peripubertal body weight and growth rate were also significantly associated with PLAG1 genotype. Growth rate per kilogram of body weight, daily feed intake, gross feed efficiency and resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 12 publications
4
62
0
3
Order By: Relevance
“…For each Q variant of the promoter present (i.e., the sequence variant proven to result in greater PLAG1 transcription levels; see above), an additional w20 kg in body weight and w2 cm in body height were observed in the cattle under investigation, resulting in a difference between full-grown QQ and qq animals of w40 kg and w4 cm (Karim et al 2011). Similarly, newborn homozygous QQ and heterozygous Qq dairy calves were found to be 18.8 and 10.4% heavier, respectively, compared to homozygous qq calves (Littlejohn et al 2012). Variants of PLAG1 have also been suggested to contribute to body size in European domestic pigs and horses (Rubin et al 2012, Metzger et al 2013, indicating that this role of PLAG1 is likely to be conserved across mammals.…”
Section: Evidence From Genome-wide Association Studiesmentioning
confidence: 96%
See 1 more Smart Citation
“…For each Q variant of the promoter present (i.e., the sequence variant proven to result in greater PLAG1 transcription levels; see above), an additional w20 kg in body weight and w2 cm in body height were observed in the cattle under investigation, resulting in a difference between full-grown QQ and qq animals of w40 kg and w4 cm (Karim et al 2011). Similarly, newborn homozygous QQ and heterozygous Qq dairy calves were found to be 18.8 and 10.4% heavier, respectively, compared to homozygous qq calves (Littlejohn et al 2012). Variants of PLAG1 have also been suggested to contribute to body size in European domestic pigs and horses (Rubin et al 2012, Metzger et al 2013, indicating that this role of PLAG1 is likely to be conserved across mammals.…”
Section: Evidence From Genome-wide Association Studiesmentioning
confidence: 96%
“…In both mouse lines, the size differences were first detected at embryonic day 11.5 and the growth retardation was maintained throughout life (or the observation period). Furthermore, the absence of an association between PLAG1 polymorphisms and growth rate relative to body weight in dairy cattle GWASs indicates that the differences in the growth rate observed in QQ and qq calves are partly due to initial differences in size, meaning that the effect of PLAG1 on growth is likely to occur mainly during fetal development (Karim et al 2011, Littlejohn et al 2012. For the trait 'post-weaning live weight' in beef cattle, epistatic interactions of the PLAG1 polymorphisms with other genes were noted, including IGF2 and Insulin (Bolormaa et al 2015).…”
Section: Possible Mechanisms Linking Plag1 To Growthmentioning
confidence: 99%
“…Pausch et al (2011);Pryce et al (2011) identified major loci affecting growth-related traits on BTA14 at 25 Mb in cattle and its orthologous region on human chromosome 8, which have been shown to be associated with adult height (Gudbjartsson et al, 2008). Littlejohn et al (2012) validated genetic effects of PLAG1 on animal size and growth in Holstein-Friesian dairy calves. Canovas et al (2014) reported two genes on BTA14 at 24 Mb associated with Brangus heifer fertility traits.…”
Section: Trait-specific Qtlmentioning
confidence: 98%
“…As the retail price of carcasses is essentially determined by its weight, beef cattle breeding programs have traditionally been focused on weight selection (GARRICK, 2011) and carcass visual scores (ARAÚJO et al, 2010) in living animals. Measurement of body weight as well as body conformation scores, carcass finishing precocity and musculature, are routinely used in beef cattle breeding programs to promote size and carcass yield improvement (TORAL et al, 2011 et al, 2013), and also appears to be associated with animals height, growth rate, back fat thickness and body size (FORTES;REVERTER, 2012;LITTLEJOHN;GRALA;SANDERS, 2012). Moreover, live weight is closely related to hot carcass weight, which is a measure obtained after slaughter, evisceration and carcass cleaning.…”
Section: According To the Brazilian Association Of Meat Exporters (Abmentioning
confidence: 99%
“…After combining the results across the nine traits with the Multi-Trait MetaAnalysis method, a total of 983 markers were declared significant at an empirical threshold of p < 9.20 x 10 -5 (Figure 1-A This chromosomal segment has been implicated as a highly pleiotropic locus underlying genetic differences in growth, weight and reproductive traits in cattle (BOLORMAA et al, 2014;FORTES;KEMPER;SASAZAKI, 2013;FORTES et al, 2012FORTES et al, , 2013KARIM et al, 2011;LITTLEJOHN;GRALA;SANDERS, 2012;UTSUNOMIYA et al, 2013UTSUNOMIYA et al, , 2014 To determine if this large segment comprised a single signal driven by a large LD block or it construed a mixture of signals, we re-analyzed our data using the same GWA model conditional on the fixed effect of the top scoring SNP. Correction for the effect of rs136543212 alone was able to remove most of the signal (Figure 2-B), which suggests that this large segment is a single LD block.…”
Section: Major Pleiotropic Effects Map To the Plag1 Regionmentioning
confidence: 99%